Wine and cheese : two products or one association? : a new method for assesing wine-cheese pairing - Galmarini, Mara Virginia (2018)
Fil: Galmarini, Mara Virginia. Centre des Sciences du Goût et de l’Alimentation. Université de Bourgogne; Francia